Restorasi Pendidikan Islam Multikultural Pesantren Sebagai Garda Depan Moderasi Beragama - Moh. Afiful Hair; Nur Syam (Institut Kariman Wirayudha Sumenep, 2023)
Indonesia as a multicultural country has a lot of potential to develop progress in various fields. These cultural differences if managed properly are expected to be able to strengthen unity and accelerate the achievement of the expected goals. However, this ideal is still in progress, so in reality there are still many conflicts arising from various backgrounds and triggering causes, both conflicts between individuals, groups, races, groups, including conflicts between religions. The strategy that can be taken is to approach the community by instilling multicultural Islamic education as an alternative resolution of inter-religious conflicts in Indonesia. One of the issues that has attracted the attention of Muslim scholars is the mainstreaming of religious moderation in Islamic boarding schools. Islamic boarding schools as the oldest and original educational institutions in Indonesia cannot be separated from these problems. This study examines the development of moderation as the basic idea of ​​pesantren. This study uses a literature review (Liberary Research) by observing the phenomenology that occurs. The results of this study First, the value of tasamuh (tolerance). The existence of these values ​​can be said to be a fundamental element in realizing multicultural educational activities. The existence of tasamuh values ​​in the realm of practice will emphasize the formation of mutual respect between people, both from differences in ethnicity, religion, and race, both inherent in individual and group life. Second, the diverse values ​​of moderation are contained in the Qur'an surah al-Baqarah: 143. Third, Islamic boarding schools are places, as well as fields for planting multicultural Islam, as guards and bastions of religious moderation in order to create seeds and a nation that is baldatun tayyibatun warabbun ghafur.